Athletic body in balance DVD - Cook, Gray, ....- (Champaign : Human kinetics, 2005)
The tests include -deep squat—assessing the mobility and stability of the hips, knees, and ankles -hurdle steps—evaluating bilateral mobility and stability of the hips, knees, and ankles -in-line lunge—determining hip mobility and stability, quadriceps flexibility, and ankle and knee stability on both sides of the body -straight leg raise—gauging hamstring flexibility -seated rotation—measuring uppertrunk stability during a combined upper- and lower-body movementMove more efficiently and achieve real gains in performance with the Athletic Body in Balance Video.
You work out and train hard. You know you can reach that next level of performance. But are you doing all that you can to get there? Adding absolute strength and power often creates muscle imbalances and mobility limitations that cause injuries and limit skill training. The Athletic Body in Balance Video is the first of its kind to show how to identify and correct muscle imbalances, mobility restrictions, and stability problems. Host Gray Cook is a physical therapist and sports conditioning expert who has proven the effectiveness of his approach through the performances of athletes in the NFL, NBA, NHL, WNBA, and Reebok® University's sports training system. Cook's methods detect where conditioning is breaking down and reveals how to get your body back on track. Included in the video are five assessment tests to help you find the imbalances in movement patterns, sample corrective exercises to improve mobility and stability, and ways to integrate these exercises into a regular training program.